Molecular Mechanisms Controlling Lymphatic Endothelial Junction Integrity - Norden, Pieter R.; Kume, Tsutomu (Frontiers in Cell and Developmental Biology, 2021)
The lymphatic system is essential for lipid absorption/transport from the digestive system, maintenance of tissue fluid and protein homeostasis, and immune surveillance. Despite recent progress toward understanding the cellular and molecular mechanisms underlying the formation of the lymphatic vascular system, the nature of lymphatic vessel abnormalities and disease in humans is complex and poorly understood. The mature lymphatic vasculature forms a hierarchical network in which lymphatic endothelial cells (LECs) are joined by functionally specialized cell-cell junctions to maintain the integrity of lymphatic vessels. Blind-ended and highly permeable lymphatic capillaries drain interstitial fluid via discontinuous, button-like LEC junctions, whereas collecting lymphatic vessels, surrounded by intact basement membranes and lymphatic muscle cells, have continuous, zipper-like LEC junctions to transport lymph to the blood circulatory system without leakage. In this review, we discuss the recent advances in our understanding of the mechanisms by which lymphatic button- and zipper-like junctions play critical roles in lymphatic permeability and function in a tissue- and organ-specific manner, including lacteals of the small intestine. We also provide current knowledge related to key pathways and factors such as VEGF and RhoA/ROCK signaling that control lymphatic endothelial cell junctional integrity.